Evaluating the Riva Business Process Architecture Identification Method and its Constituent Heuristics through their Application to a Cancer Care Organisation - Odeh, Mohammed; Green, Stewart; Kossmann, Mario; Tbaishat, Dina; Tbakhi, AbdelGhani; Mansour, Asem (2018 1st International Conference on Cancer Care Informatics (CCI), 2018)
The Riva method identifies an organisation's business process architecture. Unfortunately, the research literature does not contain evidence that the heuristics used in the method's key steps have been validated. To begin to address this shortcoming, the co-researchers have applied Riva to aspects of the cancer care domain at the King Hussein Cancer Center (KHCC) in Amman, Jordan. A subset of the results was presented to KHCC domain experts, who were invited to evaluate the validity and completeness of the heuristics used in each of the method's steps. Their evaluation indicates that the large majority of the heuristics associated to the various steps of the method was seen as valid; with the exception that there was a perceived lack of specific guidance by means of heuristics related to Case Strategy Processes.